Brand Image Mediation in Coffee Shop Consumer Decisions: Marketing Mix Effects in Indonesia - Mochamad Malik Akbar Rohandi; Allya Roosallyn Assyofa; Putri Fariska; Ratih Hurriyati (Research Synergy Foundation, 2026)
Indonesia’s coffee shop industry has experienced rapid expansion, driven by shifting consumer lifestyles and intensified market competition. In this digitally mediated competitive landscape where social media promotions, online ordering platforms, and e-wallet-based discounts shape consumer engagement understanding the determinants of purchase decisions becomes critical. The mediating pathways through which marketing mix elements influence these decisions remain insufficiently examined, particularly the role of brand image in emerging markets. This explanatory quantitative study employs Structural Equation Modeling–Partial Least Squares (SEM-PLS) to investigate the direct and indirect effects of price discount, store atmosphere, service quality, and product assortment on purchase decisions, with brand image as the mediating variable. Primary data were collected through structured questionnaires from 100 purposively sampled respondents in Bandung, Indonesia, who had recent coffee shop purchase experience. Results demonstrate that product assortment significantly influences purchase decisions directly, while price discount, store atmosphere, and service quality show no significant direct effects. However, price discount substantially impacts purchase decisions through brand image mediation, with the model explaining 96.3% of brand image variance and 87.4% of purchase decision variance. These findings advance strategic marketing theory by demonstrating that brand image functions as a critical mediating mechanism consistent with the Stimulus, Organism and Response (S–O–R) framework transforming price-based stimuli into actual purchase behavior. Practically, coffee shop managers should implement dual-focus strategies: cultivating brand perceptions through strategic discounting while simultaneously diversifying product offerings to stimulate purchase decisions directly.